Subjugated and Anguished Identity: The Indian Trilogy by V. S. Naipaul: Re-imagining India through V. S. Naipaul's Trilogy (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Since 1857, the date of the first war for independence in India, the nation has seen different socio-political, economic and historical changes, and the upturns have influenced the nation and the idea of nation internally as well as globally. Race, culture and milieu have dependably been the essential wellspring of literature and their impressions are especially evident in each field whether it is science, religion or logic. India has been the land of extraordinary men like Lord Ram and Lord Krishna as is apparent in Hindu mythology however the truth of the matter is that they were required in their particular times. Travel writings are considered as a genre of literature, yet the truth of the matter is very unique. Travelogues are the reflections and replications of contemporary socio-social and ethnic societies in which they were recorded. This paper examines the 'nation' from an emigrant's point of view. By scrutinizing the Identity of India, past topography and place, the perspective of the emigrant expands the structure inside which India is characterized. Through a careful perusing of V S Naipaul's trilogy on India, it will be contended how his perspective hits on undecided relationship with his involvement in India how feelings of delicacy and joy compete with the energy and foolishness of a colonialist. In this paper we will study about the revolution that came in the life of the Indian Migrants through the eyes of V S Naipaul.